Risk of total metachronous advanced neoplasia at surveillance colonoscopy after detection of serrated lesions: a matched case–cohort study - Djinbachian, Roupen; Lafontaine, Marie-Lyssa; Anderson, Joseph C.; Pohl, Heiko; Dufault, Talia; Boivin, Michel; Bouin, Mickael; von Renteln, Daniel (Endoscopy, 2023)
Background Serrated lesions are potential colorectal cancer precursors. This study evaluated the presence of total metachronous advanced neoplasia (T-MAN) at follow-up in patients with index serrated lesions compared with a matched cohort without serrated lesions.Methods Patients aged 45–74 years with serrated lesions were matched 2:1 by sex, age, synchronous polyps, and timing of index colonoscopy, to patients without serrated lesions. The primary outcome was T-MAN (advanced adenoma or high-risk serrated lesion) at follow-up. Secondary outcomes included presence of T-MAN stratified by synchronous polyps and serrated lesion characteristics.Results 1425 patients were included (475 patients, 642 serrated lesions; 950 controls; median follow-up 2.9 versus 3.6 years). Patients with serrated lesions had greater risk of T-MAN than those without (hazard ratio [HR] 6.1, 95 %CI 3.9–9.6). Patients with serrated lesions and high-risk adenoma (HRA) had higher risk of T-MAN than those with HRA alone (HR 2.6, 95 %CI 1.4–4.7); similarly, patients with serrated lesions plus low-risk adenoma (LRA) had higher risk than those with LRA alone (HR 7.0, 95 %CI 2.8–18.4), as did patients with serrated lesions without adenoma compared with no adenoma (HR 14.9, 95 %CI 6.5–34.0). Presence of proximal sessile serrated lesion (SSL; HR 9.3, 95 %CI 5.4–15.9), large SSL (HR 17.8, 95 %CI 7.4–43.3), and proximal large SSL (HR 25.0, 95 %CI 8.8–71.3), but not distal SSL, were associated with greater risk for T-MAN.Conclusion Patients with serrated lesions had higher risk for T-MAN regardless of synchronous adenomas. Patients with serrated lesions and HRA, and those with large or proximal SSLs, were at greatest risk.